L’impact du choix de la langue sur les débouchés et carrières professionnels : points de vue d’étudiants - Abdellatif Bensfia; Abdelouahed Mabrour; Khalil Mgharfaoui (Recherches en didactique des langues et des cultures)
French in Morocco is closely related to scientific and technological progress, modernity and professional success. It is a very serious rival to Arabic on the job market. French remains the language of work, economics and business. Mastery of French offers a huge competitive advantage. However, the Moroccan school system does not handle the language issue merely from a functional point of view. Its mission is not only to train for employment but also to protect a fundamental cultural heritage and identity represented by Arabic. By providing similar training in both languages in some programs, the Moroccan university system highlights the contrast between employment and identity. The survey we conducted shows that.